The Artificial Tree: Integrating Microalgae into Sustainable Architecture for CO2 Capture and Urban Efficiency—A Comprehensive Analysis - Rosa Cervera; María Rosa Villalba; Javier Sánchez (Buildings)
The Artificial Tree project, developed by the authors, presents an innovative approach to urban sustainability by integrating microalgae cultivation systems for CO2 capture, biomass production, and urban cooling. This study evaluates the project’s feasibility and effectiveness in transforming urban furniture into functional photobioreactors that enhance environmental quality. Inspired by natural aesthetics, the Artificial Tree functions as both a CO2 sink and a biofertilizer producer. Using Scenedesmus microalgae, the system captures 50 kg of CO2 annually per unit and generates 28 kg of biomass, which further reduces emissions when utilized as a biofertilizer. To assess its impact, a multi-criteria decision analysis (MCDA) method was employed, considering factors such as CO2 capture, biomass production, social engagement, visual appeal, and scalability. This methodology incorporated a three-level qualitative scale and criteria tailored to compare similar projects with at least three months of operation and available data on microalgae productivity. Results highlight that the Artificial Tree achieves up to 2.5 times more CO2 fixation than a mature tree while combining environmental benefits with public engagement. Its modular and aesthetic design supports educational outreach and inspires larger-scale implementation. This project demonstrates significant potential to redefine urban spaces sustainably by seamlessly integrating functionality, artistic expression, and public interaction.